Mahram Pada Safar Perempuan Dalam Tinjauan Sosiologis (Menjembatani Realitas Muslim Klasik dan Kekinian) - Permana, Aramdhan Kodrat (Musawa Jurnal Studi Gender dan Islam, 2010)
The idea of the inclusion of mahram for women travelling is an alternative and necessary instrument for the safety and comfort of women. This article anlayzes the concept ogf mahram from a sociological perspective. Socio. historically argue that the hadits of mahram was produced by the Prophet to guarantee the safety of women while they travelling. Mahram here functions like the security guard for the women. In understanding the hadith in our today's context, the rationale or "illah" of this hadits should be taken into account. Sociologically we might find significances of re-eaxamining the concept of mahram and women travelling. At least two significances arise: 1) Changes in women's capacity and roles; 2) Development of the security system, from one which based on human person to regulationas and advancement of transportation technology.